Rhetoric in the American and Cuban palaver on human trafficking - Rand, Marcus (2010)
The purpose of the thesis is to understand how the anti-human trafficking dialogue in the Cuban-American context is used as medium to express national agendas. The research data were speeches delivered by representatives of the US and Cuban governments that specifically mentioned Cuba or the United States in addition to human trafficking. The broad categories that emerged in these speeches included religion, morality, children (youth), and gender. The rhetoric employed within each of these categories was examined to reveal how the palaver on human trafficking was used to promote American and Cuban agendas.